1995
DOI: 10.1029/95ja00574
|View full text |Cite
|
Sign up to set email alerts
|

Satellite remote sensing of thermospheric O/N2 and solar EUV: 1. Theory

Abstract: Simultaneous measurements of disk‐viewing OI 135.6 nm and N2 Lyman‐Birge‐Hopfield (LBH) dayglow can be used to monitor the solar EUV flux QEUV and the column abundance of thermospheric O relative to N2 (O/N2). We report on a study that quantifies the relationships between these emissions and the above parameters. Emission is considered from 134.5 to 139.0 nm (designated 135.6 nm) and from 155.0 to 170.0 nm (designated as LBH) at a resolution of 3.6 nm. The intervals and resolution were chosen for analysis of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
293
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 180 publications
(294 citation statements)
references
References 26 publications
1
293
0
Order By: Relevance
“…The FUV dayglow, which extends down to ∼100 km in the Earth's atmosphere, can be observed by satellite instruments against Earth's disk, since pure absorption (extinction) by O 2 attenuates the emission arising from below that altitude. Strickland et al [1995] describe the utilization of OI 135.6 nm and LBH dayglow observations to specify Q EUV , the term they used to designate the solar EUV irradiance from 0-45 nm that produces the terrestrial FUV dayglow, as well as SO/N 2 (the vertical column density ratio referenced to a fixed column value for N 2 ).…”
Section: Comparisons With the Terrestrial Dayglowmentioning
confidence: 99%
See 1 more Smart Citation
“…The FUV dayglow, which extends down to ∼100 km in the Earth's atmosphere, can be observed by satellite instruments against Earth's disk, since pure absorption (extinction) by O 2 attenuates the emission arising from below that altitude. Strickland et al [1995] describe the utilization of OI 135.6 nm and LBH dayglow observations to specify Q EUV , the term they used to designate the solar EUV irradiance from 0-45 nm that produces the terrestrial FUV dayglow, as well as SO/N 2 (the vertical column density ratio referenced to a fixed column value for N 2 ).…”
Section: Comparisons With the Terrestrial Dayglowmentioning
confidence: 99%
“…Strickland et al [1995] showed that this solar energy between 0 and 45 nm, termed Q EUV , closely tracks independent solar EUV irradiance observations made by the Solar EUV Monitor (SEM) on the Solar Heliospheric Observatory (SOHO) on time scales of flares and solar rotation [Strickland et al, 2004[Strickland et al, , 2007. Furthermore, the incompatibility of Q EUV and large irradiance increases during flares present in the SEE version 8 data motivated revision of SEE observations.…”
Section: Introductionmentioning
confidence: 99%
“…These techniques are applicable to ICON FUV. In addition to atmospheric composition and temperature GUVI data was also used to infer the geo-effective EUV solar irradiance (Strickland et al 1995), which was compared to simultaneous Solar Extreme EUV (SEE) measurements on TIMED. It appears that the EUV flux estimated from GUVI measurement was on average 30% lower than the SEE measurement and varied less with solar activity.…”
Section: Space Based Observations Of the Atmosphere In The Fuvmentioning
confidence: 99%
“…The algorithm, a uniqueness study, and two initial applications are being reported. The algorithm extends the works of Meier et al [1995] and Strickland et al [1995], who used the Atmospheric Ultraviolet Radiance Integrated Code (AURIC)model [Strickland et al, 1998] to calculate the needed excitation rates and the REDISTER model of Gladstone [1982,1988] The choice of reference level must be dictated by the uniqueness of the derived parameter to the observations, which in turn is dictated by the physics related to the observing conditions. The physics argues for a reference level in terms of N 2 since, as noted above, variations in the observed signal reflect competition between O and N 2 for photoelectron energy.…”
Section: Introductionmentioning
confidence: 99%